A POGLUT1 mutation causes a muscular dystrophy with reduced Notch signaling and satellite cell loss. Issue 11 (10th October 2016) - Servián‐Morilla, Emilia; Takeuchi, Hideyuki; Lee, Tom V; Clarimon, Jordi; Mavillard, Fabiola; Area‐Gómez, Estela; Rivas, Eloy; Nieto‐González, Jose L; Rivero, Maria C; Cabrera‐Serrano, Macarena; Gómez‐Sánchez, Leonardo; Martínez‐López, Jose A; et al.
Abstract: Skeletal muscle regeneration by muscle satellite cells is a physiological mechanism activated upon muscle damage and regulated by Notch signaling. In a family with autosomal recessive limb‐girdle muscular dystrophy, we identified a missense mutation in POGLUT1 (protein O ‐glucosyltransferase 1), an enzyme involved in Notch posttranslational modification and function. In vitro and in vivo experiments demonstrated that the mutation reduces O ‐glucosyltransferase activity on Notch and impairs muscle development. Muscles from patients revealed decreased Notch signaling, dramatic reduction in satellite cell pool and a muscle‐specific α‐dystroglycan hypoglycosylation not present in patients' fibroblasts. Primary myoblasts from patients showed slow proliferation, facilitated differentiation, and a decreased pool of quiescent PAX7 + cells. A robust rescue of the myogenesis was demonstrated by increasing Notch signaling. None of these alterations were found in muscles from secondary dystroglycanopathy patients. These data suggest that a key pathomechanism for this novel form of muscular dystrophy is Notch‐dependent loss of satellite cells. Synopsis: A protein O ‐glucosyltransferase 1 ( POGLUT1 ) homozygous D233E mutation underlies a novel autosomal recessive muscular dystrophy, wherein altered Notch signaling affects muscle regeneration and, as a consequence, α‐dystroglycan glycosylation. POGLUT1 D233E exhibits decreased enzymatic activity toward Notch EGF repeats. POGLUT1 D233E leads to Notch activity downregulation, which affects muscle regeneration due to satellite cell (SC) loss of quiescence, depletion of PAX7 + cells, and premature and enhanced differentiation. Reduced Notch signaling accelerates muscle differentiation and disrupts the progressive and coordinated process of α‐dystroglycan glycosylation during differentiation, and hence, mild α‐dystroglycan hypoglycosylation is observed in skeletal muscle from POGLUT1 D233E patients. Defective regeneration, combined with α‐dystroglycan hypoglycosylation, likely results in skeletal muscle degeneration and finally gives rise to muscular dystrophy. Abstract : A protein O ‐glucosyltransferase 1 ( POGLUT1 ) homozygous D233E mutation underlies a novel autosomal recessive muscular dystrophy, wherein altered Notch signaling affects muscle regeneration and, as a consequence, α‐dystroglycan glycosylation.